A metalinguagem na crônica de Drummond - Silva, Maria Isabel da (2008)
This essay focuses in the most important process of the articulation of a text, connected in two levels: - syntactic structure and the semantic arrangement. It s around these two axes that the linguistic and speech procedures are explored, axes that are responsible for the meaning of the text. Owing to this, some proposals of the textual linguistics which are concerned about the mainly criteria of textuality and cognitive process have been employed. This essay will focus only on the study of linguistic operations responsible for the production, construction and procedures of texts, whose language is used as metalinguistics. It s also concerned about the surface linking on the level on linguistic components, the conceptual coherence on semantics and cognitive and the pragmatic one, on the level of actions and intentions. The objects of study are short stories written by Carlos Drummond de Andrade, which explore metalinguistic function.